INTERNAL ASPECTS OF CHINESE POLICY IN THE 1950S – LATE 1960S: THE NATIONAL QUESTION, THE SEARCH FOR WAYS OF DEVELOPMENT AND THE PROBLEMS OF HISTORY (American Journal of Interdisciplinary Research and Development, 2022)
This article reveals some aspects of China's internal policy in the 1950s and late 1960s. Particular attention is paid to the national policy of China in relation to other peoples living in the country, the choice and search for ways of development, and the problems of history, with the help of geopolitics, sociology, Sinology, Oriental studies and the application of scientific results of domestic, foreign and Chinese researchers.